2009
DOI: 10.1590/s0103-50532009000800005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural characterization of block and random low molecular weight copolymers composed of L-lactic acid and isosorbide succinate moieties

Abstract: Resíduos de succinato de isosorbídeo foram incorporados na cadeia principal de poli(L-lactídeo) (PLLA) visando a obtenção de uma nova classe de polímeros biodegradáveis com propriedades melhoradas. Este artigo descreve a síntese e caracterização de quatro tipos de copolímeros de baixa massa molar. O copolímero I foi obtido da mistura dos monômeros L-lactídeo, isosorbídeo e anidrido succínico; II do oligo(L-lactídeo) (PLLA), isosorbídeo e anidrido succínico; III do oligo(succinato de isosorbídeo) (PIS) e L-lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Random copolymers of l -lactic acid and isosorbide succinate moieties, 96 styrene oxide (SO) and allylglycidyl ether (AGE), propylene oxide (PO) or isopropyl glycidyl ether (IPGE) 97 and poly(styrene- co -4-vinylpyridine) 98 were verified by MALDI-TOF-MS. Schubert reported characterization of different poly(2-oxazoline) block copolymers by MALDI-TOF-MS, and revealed the desired polymer structure and possible polymerization mechanisms. 99 The crossover reaction during ROMP block copolymerization of 3-methyl-3-phenylcyclopropene and norbornene derivatives was investigated using MALDI-TOF-MS by Binder et al 100 Samperi et al applied MALDI-TOF-MS to characterize the linear-hyperbranched hybrid poly(butylene adipate) (HPBA) copolymers.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Random copolymers of l -lactic acid and isosorbide succinate moieties, 96 styrene oxide (SO) and allylglycidyl ether (AGE), propylene oxide (PO) or isopropyl glycidyl ether (IPGE) 97 and poly(styrene- co -4-vinylpyridine) 98 were verified by MALDI-TOF-MS. Schubert reported characterization of different poly(2-oxazoline) block copolymers by MALDI-TOF-MS, and revealed the desired polymer structure and possible polymerization mechanisms. 99 The crossover reaction during ROMP block copolymerization of 3-methyl-3-phenylcyclopropene and norbornene derivatives was investigated using MALDI-TOF-MS by Binder et al 100 Samperi et al applied MALDI-TOF-MS to characterize the linear-hyperbranched hybrid poly(butylene adipate) (HPBA) copolymers.…”
Section: Applicationsmentioning
confidence: 99%
“…85 This MS technique was also used for monitoring other homopolymers with different structures, such as poly(dendrimer)s, 86 poly(2-oxazoline), 87 poly(ethylene glycol), and allyl(1-ethoxyethoxy)-PEG-OH, 88 as well as uorotelomer-based acrylate polymers (FTACPs), 89,90 trimethylene carbonate, 91 poly(methyl methacrylate) (PMMA), 92 linear 3-polylysine, 93 poly(butoxycarbonylaminomethyl acrylate) (PtBAMA) homopolymer, 94 poly(1.2-butylene oxide)-diol (PBOdiol) 95 and so on. Random copolymers of L-lactic acid and isosorbide succinate moieties, 96 styrene oxide (SO) and allylglycidyl ether (AGE), propylene oxide (PO) or isopropyl glycidyl ether (IPGE) 97 and poly(styrene-co-4-vinylpyridine) 98 were veried by MALDI-TOF-MS. Schubert reported characterization of different poly(2oxazoline) block copolymers by MALDI-TOF-MS, and revealed the desired polymer structure and possible polymerization mechanisms. 99 The crossover reaction during ROMP block copolymerization of 3-methyl-3-phenylcyclopropene and norbornene derivatives was investigated using MALDI-TOF-MS by Binder et al 100 Samperi et al applied MALDI-TOF-MS to characterize the linear-hyperbranched hybrid poly(butylene adipate) (HPBA) copolymers.…”
Section: Characterization Of Homopolymers and Copolymersmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Isosorbide is obtained by dehydration of D-sorbitol and produced worldwide at a rate of 650 000 tons per annum. 16,17 Isosorbide is thermally stable, available in large quantities and useful for the synthesis of bio-based polymers, such as polyesters, [18][19][20][21][22][23][24][25][26][27][28] polyamides 29 and polyurethanes. [30][31][32][33][34][35][36] A polycarbonate derived from petroleum is a bisphenol A-based polycarbonate (BPAPC).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Many studies reported the synthesis of functional monomers and oligomers based on isosorbide (IS), which belongs to 1,4;3,6-dianhydrohexitols, [5][6][7][8] known as renewable and sustainable OH-functional monomers. [9][10][11][12] The scope of this study is the synthesis of new bio-based dihydroxy functional oligomers of polyethersulfones (PES) based on IS as precursor of biomaterials.…”
Section: Introductionmentioning
confidence: 99%